Comparison of corporate behaviors in favor of honest and liar spokes (Research, Society and Development, 2022)
Objective: To compare body movements between honest and false discourses. Method: A quantitative and transversal study, with descriptive and analytical approaches, performed with 40 subjects equally distributed in two groups regarding sex. The participants did not present evidences of deficiency (auditory, visual, physical or neuromotor), they remained with the hair fixed and seated during the filming of the narrative of the true and false speeches, being interpreted previously the basic movements of each subject. The obtained data were analyzed, compared and submitted to the statistical analysis in the SPSS program using the univariate and bivariate techniques and the Chi-square and Fisher Exact tests, with significance level p